Transmission of Point Chirality to Axial Chirality for Strong Circular Dichroism in Triarylmethylium-o,o-dimers - Ishigaki, Yusuke; Iwai, Tomohiro; Hayashi, Yuki; Nagaki, Aiichiro; Katoono, Ryo; Fujiwara, Kenshu; Yoshida, Jun-ichi; Suzuki, Takanori (Synlett, 2018)
Triarylmethylium-o,o-dimers adopt a twisted geometry so that two diarylmethyliums are stacked in a slipped manner. Thus, chiral auxiliaries on the aryl groups induce a preference in the axial chirality of the central biphenyl unit. Strong circular dichroism is attained through exciton coupling, which can be used for additional spectral output in their electrochromic behavior. Diastereoselectivity based on π–π stacking exhibits unique solvent effects, thus endowing multifunctional response properties.
Keywords: chiral induction; axial chirality; exciton coupling; redox system; electrochromism; flow microreactor; dication; dye